Mindset Shift in Cyber Pedagogy: A Teacher's Strategy upon Learning from Home - Denny Kodrat (Islamic Research, 2020)
As Covid 19 pandemic hits Indonesia, teaching-learning activities change dramatically. Learning from home becomes the only alternative in conducting distance education. From the earlier, this cyber pedagogy is assumed as an emergency step taken by the government. Consequently, teachers hold the learning process without clear objectives. Many complaints have occurred, and some improvements are proceeded to reinvent the quality of education. As a radical response toward the chaotic situation, this article is aimed at investigating two significant issues. The first is the requirement of mindset shift as the way to solve the cyber pedagogical problem. The second is the teachers' strategy in doing online learning. Theories about distance learning and quality are referred to as library research does. A descriptive qualitative approach was carried out, and in-depth interviews with parents, students, and teachers were taken. The result of the discussion is the mindset shift in teachers, parents, and stakeholders is required. The creative teachers who have good literacy in information technology are needed in running e-learning and conduct interactive learning from home.